2006
DOI: 10.1016/j.bbabio.2006.10.003
|View full text |Cite
|
Sign up to set email alerts
|

CO-dependent H2 evolution by Rhodospirillum rubrum: Role of CODH:CooF complex

Abstract: Upon exposure to CO during anaerobic growth, the purple phototrophic bacterium Rhodospirillum rubrum expresses a CO-oxidizing H(2) evolving enzymatic system. The CO-oxidizing enzyme, carbon monoxide dehydrogenase (CODH), has been purified and extensively characterized. However the electron transfer pathway from CODH to the CO-induced hydrogenase that evolves H(2) is not well understood. CooF is an Fe-S protein that is the proposed mediator of electron transfer between CODH and the CO-induced hydrogenase. Here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 42 publications
2
46
0
Order By: Relevance
“…gelatinosus chromatophore membranes following CO treatment (data not shown). The Western blotting data on the wild-type strain are therefore in agreement with and complement the studies of R. rubrum showing that the hydrogenase genes are transcriptionally induced by CO (12), with a concomitant accumulation of the CooH protein (34). The Western blots confirmed the absence of CooH in GV1762 following a 4-h CO treatment and its restoration in GV1762c.…”
Section: Vol 76 2010 Characterization Of Genes In Rubrivivax Gelatisupporting
confidence: 77%
“…gelatinosus chromatophore membranes following CO treatment (data not shown). The Western blotting data on the wild-type strain are therefore in agreement with and complement the studies of R. rubrum showing that the hydrogenase genes are transcriptionally induced by CO (12), with a concomitant accumulation of the CooH protein (34). The Western blots confirmed the absence of CooH in GV1762 following a 4-h CO treatment and its restoration in GV1762c.…”
Section: Vol 76 2010 Characterization Of Genes In Rubrivivax Gelatisupporting
confidence: 77%
“…Interestingly, it seems to be a component of the CO-oxidizing system, since it is coupled to the carbon monoxide dehydrogenase gene (CODH). A similar COoxidation/H 2 -evolution enzyme complex, associated with [NiFe] hydrogenase, was found in the membrane of Rhodospirillum rubrum and has been described as allowing the bacterium to metabolize carbon monoxide in the reaction CO+H 2 O A CO 2 +H 2 (Singer et al, 2006). Neither hydrogenase nor the CODH subunit are predicted membrane proteins in C. bolteae, therefore a function as a putative energy coupling site is hypothetical.…”
Section: The Monomeric [Fefe] Hydrogenases Of Group Amentioning
confidence: 95%
“…In nitrogen-fixing bacteria, e.g. Azotobacter chroococcum, [NiFe] hydrogenase is induced when hydrogen is produced as an intrinsic part of nitrogenase (Yates et al, 1997 A small group of multisubunit membrane-associated [NiFe] hydrogenases, closely related to proton-pumping NADH : ubiquinone oxidoreductase (complex I), has been identified in several organisms including Escherichia coli (hydrogenases 3 and 4; Maeda et al, 2007;Self et al, 2004), Rhodospirillum rubrum (Singer et al, 2006), Methanosarcina barkeri (Kurkin et al, 2002) and Desulfovibrio gigas (Rodrigues et al, 2003). These have been assigned to group 4 described by Vignais et al (2001), which is characterized by membrane-associated H 2 -evolving respiratory [NiFe] hydrogenases.…”
Section: Hydrogenasesmentioning
confidence: 99%
“…Also, in CO-grown cells, the marked expression of monofunctional CODH (TON_1018), homologous to CooS and CooF (TON_1017), indicates the possibility that T. onnurineus NA1 can evolve H 2 during growth on CO, as displayed by Rhodospirillum rubrum (68) and Carboxydothermus hydrogenoformans (69,70). In addition, it has been reported that energy-converting hydrogenase-type hydrogenases couple the formation of H 2 to the generation of the proton motive force that drives ATP synthesis (66,71).…”
Section: Analysis Of One-carbon Metabolism In T Onnurineus Na1mentioning
confidence: 99%